2020
DOI: 10.1097/ico.0000000000002376
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Study of Keratoconus Progression in Patients Awaiting Corneal Cross-linking

Abstract: Purpose: Keratoconus progression should be treated with corneal cross-linking (CXL) in a timely manner. This study aimed to investigate patient factors associated with keratoconus progression between time of listing and at time of CXL. Methods: Prospective observational study at a tertiary center. Ninety-six eyes of 96 patients with keratoconus. Demographic, clinical, and tomographic parameters were analyzed to determine the risk factors for keratoconus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…As expected, the percentage of triplets categorized as suspect progressive here (48%) is higher than the rates of clinically meaningful progression in recent studies [ 38 , 39 ]. We also note that had one-sided confidence intervals been used [ 7 ], 1.96 would have to be replaced by 1.64 in the formula, narrowing the 95 CI and increasing the percentage of suspect progressive cases.…”
Section: Discussionsupporting
confidence: 71%
“…As expected, the percentage of triplets categorized as suspect progressive here (48%) is higher than the rates of clinically meaningful progression in recent studies [ 38 , 39 ]. We also note that had one-sided confidence intervals been used [ 7 ], 1.96 would have to be replaced by 1.64 in the formula, narrowing the 95 CI and increasing the percentage of suspect progressive cases.…”
Section: Discussionsupporting
confidence: 71%
“…The ability of OCT to diagnose early keratoconus otherwise not detectable on clinical and tomographic evaluation may assist in expediting early treatment and preventing disease progression [20]. This can potentially mitigate delays that can occur due to the high need for CXL in certain populations [5]. Epithelial changes on OCT are thought to be the first detectable sign of ectasia, representing an initial epithelial compensation in response to underlying stromal changes [10].…”
Section: Discussionmentioning
confidence: 99%
“…Corneal topography has long been the mainstay of diagnosis, staging, and progression analysis in this clinical entity, but in recent years, epithelial thickness (ET) maps have played an increasingly more prominent role in the early detection of subclinical cases [2]. Previous studies have shown that early detection of keratoconus with timely cornea crosslinking (CXL) can halt the progression of the disease, maintain or improve visual acuity and lead to a reduction in the number of patients requiring keratoplasty [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This will help to identify at risk individuals/populations, optimize long-term management of the affected population, and provide appropriate access to modalities such as contact lenses (CLs), corneal crosslinking (CXL), and corneal transplantation. 22,23 Advances in rigid gas permeable (RGP) lens technologies have made it possible for most cases of keratoconus to be managed by community optometrists, thus an investigation focused on these cases would likely encompass a large proportion of the population with keratoconus. The Aotearoa Research into Keratoconus (ARK) study focused on subjects with keratoconus managed by optometrists in NZ.…”
mentioning
confidence: 99%